Content Marketing Impact on Consumer Purchase Decision Through Purchase Intention of Skintific Skincare Products - Palulungan, Josep; Angliadi, Kenneth; Asalui, Andrew (Manajemen FEB Unima, 2025)
Technological advancement creates an easement for customers to meet their expectations with the products available and creates a pool of followers with the usage of social media and ultimately creates a fanbase where the product information travels as fast as the social media traffic. The purpose of this research is to determine the role of content marketing on the purchase decision of Skintific skincare products, with purchase intention as a mediating variable. The type of research method used in this observation is a quantitative method. The respondents of this research are consumers who have bought any Skintific skincare product and consumers who have already viewed any Skintific social media content. The respondents of this research are spread around the Manado City area. Based on the result using SmartPLS 4.0, content marketing directly and significantly influences purchase decision, content marketing significantly influences purchase intention, and purchase intention significantly influences purchase decision. Lastly, content marketing significantly influences purchase decisions through the purchase intention of the Skintific skincare product. The management must enhance the metrics of the variables provided to reach the optimal level of purchase decision.